Cuminum cyminum Extracts as Eco-Friendly Corrosion Inhibitor for Mild Steel in Seawater. (7th February 2013) - Sribharathy, V.; Rajendran, Susai
Abstract : The inhibitive effect of Jeera (Cuminum cyminum) plant extracts on the corrosion of mild steel in an aqueous solution of seawater was investigated using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The stability of the inhibition efficiency of Jeera extracts was examined by weight-loss method. Potentiodynamic polarization curves indicated that the Jeera extract behaves as an anodic type inhibitor. EIS measurements showed that the dissolution process occurs under activation control. The corrosion rates of steel and the inhibition efficiencies of the extract obtained from impedance and polarization measurements were in good agreement. Inhibition was found to increase with an increasing concentration of the plant extract. The results obtained show that the Jeera extract could serve as an effective inhibitor for the corrosion of mild steel in seawater.